Contributions du Laboratoire Conchylicole de Poitou-Charente au défi MOREST en 2002. Thématique "Ecologie côtière" - Soletchnik, Patrick; Le Moine, Olivier; Faury, Nicole; Guilpain, Patrice; Geairon, Philippe; Razet, Daniel; Madec, Patrick; Robert, Stephane; Taillade, Sylvie; Doner, Anne (2003)
This report presents results obtained by the LCPC in coastal Ecology. The contributions of the LCPC, as partner associated with the genetic studies, do not appear in this report. This report is divided in 5 parts of differing importance : • Task 2.2.3. A "multi-disciplinary study of the DYNAmics of estival mortalities of Crassostrea gigas in the Marenne - Oléron Basin (Dynamo-2002)"; study developed and directed by the LCPC after the “plat-table” C. gigas mortality model in the Marennes- Oleron Basin. • Task 2.3 . "Influence of autumn and winter conditions on the maturation of parents (phase 1) and on the survival of their offspring (phase 2) (Gegen). Action directed by the LCPC. • Task 2.2.1. " Dynamics of mortality, reproduction and spawning. Intersite Comparisons" : Contributions by the LCPC and the LCN to a specific multi-field study on biological and environmental responses between Bay des Veys and Marenne - Oléron Basin. • Initial approach of a comparison between two oyster sites : the Bay of Veys (Low Normandy) and the Marenne - Oléron Basin (Charente Maritime) from 1997 to 2002. A previously unplanned study developed by the LCN and LCPC. • Preliminary genetic characterization of families. A previously unplanned contribution carried out in collaboration between the LCPC and LGP. Ce rapport présente les résultats obtenus par le LCPC dans le cadre de la thématique Ecologie côtière. La contribution du LCPC, comme partenaire associé aux études de génétique n'apparaît pas dans ce rapport. Ce rapport est constitué de 5 parties d'inégales importances, reprenant des tâches précises du défi : • La tâche 2.2.3. "Étude pluridisciplinaire de la DYNAmique des Mortalités estivales de Crassostrea gigas dans le Bassin de Marennes - Oléron (Dynamo-2002)"; Etude créée et pilotée par le LCPC autour du modèle de mortalité "plat-table" du Bassin de Marennes Oléron. • La tâche 2.3 . "Influence des conditions automnales et hivernales, sur la maturation des géniteurs (phase 1) et sur la survie de leur descendance (phase 2) ...